Serum IgM antibody response to Clostridioides difficile polysaccharide PS-II vaccination in pony foals. (October 2022) - Arroyo, Luis G.; Hodgins, Douglas C.; Guest, Bruce; Costa, Marcio; Ma, Zuchao; Monteiro, Mario A.
Abstract: Objectives: Clostridioides difficile (formerly Clostridium difficile ) is associated with colitis in foals and mature horses. C. difficile exposes specific phosphorylated polysaccharides (PSs), named PS-I, PS-II and PS-III. These cell-surface PSs are potential vaccine targets, especially the hexasaccharide phosphate PS-II, that has been found in all C. difficile ribotypes examined. Since we previously identified anti-PS-II circulating antibodies in horses, we postulated that vaccinating foals with PS-II may prevent colonization by C. difficile . In this study, we aim to evaluate the IgM antibody responses in foals to PS-II. Methods: To evaluate the reactogenicity and immunogenicity of C. difficile PS-II in foals, three-to four-month-old foals were vaccinated intramuscularly three times at intervals of three weeks with 100 μg/dose (3 foals) or 500 μg/dose (3 foals) of purified PS-II antigen with aluminum hydroxide adjuvant, or with a placebo preparation (2 foals) containing adjuvant alone. Results: No injection site swelling, pain or fever was observed after vaccination. Two of the three foals receiving 100 μg/dose, and three out of three foals receiving 500 μg/dose of PS-II responded with increases in serum IgM antibodies. No control foals that received the placebo had IgM responses to PS-II. There was a trend towards a higher response rate in foals receiving 500 μg PS-II one week after second vaccination when compared to control foals and towards higher concentrations of serum IgM antibodies in foals receiving 500 μg PS-II. Conclusions: No adverse reactions were observed following vaccination with PS-II in foals; Serum IgM immune responses were induced by vaccination. A polysaccharide-based vaccine for C. difficile in horses deserves further investigation. Highlights: Clostridioides difficile polysaccharide PS-II is immunogenic in foals. Vaccination of foals with C. difficile PS-II raises anti-PS-II serum IgM antibodies. No adverse reactions were observed following vaccination with PS-II in foals.